RESEARCH ON THE EFFICIENCY OF USING HYDRO TURBINES IN PUMPING MODE AND FOR ELECTRICITY GENERATION - Murodov, Rivojiddin; Quchqarov Akmaljon; Boynazarov Bekzod; Uzbekov Mirsoli (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article explores the prospects for developing a hydro turbine pump operation and electricity generation system using water flow energy. The system under investigation utilizes a hydro turbine that converts the kinetic energy of water into mechanical energy. This energy is transmitted simultaneously to the water pump and the electricity generator via a reducer. The study analyzes the efficiency of this dual-function system and identifies the optimal parameters for water resource management and energy production. The article evaluates various hydro turbine configurations, flow speeds, and system parameters, determining the most favorable conditions for maximum energy extraction and water lifting efficiency. Additionally, the practical application of such systems in areas with abundant water resources is discussed.